Study on the influence of natural cracks on the mechanical properties and fracture mode for shale at the microscale: An example from the Lower Cambrian Niutitang Formation in northern Guizhou - Yang, Chao; Wu, Zhonghu; Wang, Wentang; Qu, Heng; Ren, Nuo; Li, Hai (Frontiers in Earth Science, 2023)
A large number of natural cracks exist in shale reservoirs, and the presence of natural cracks weakens the integrity of shale, which is an important factor affecting the effectiveness of shale gas extraction. In this paper, the shales of the Lower Cambrian Niutitang Formation in northern Guizhou were scanned by electron microscopy, their microstructures were selected for digital image processing, and uniaxial compression numerical tests were conducted on shale models containing different natural crack dips using the rock fracture process system RFPA2D-DIP to study the effects of natural cracks on the mechanical properties and fracture patterns of shales at the microscopic scale. The study shows that the peak strength and elastic modulus of the shale increase with in-creasing natural crack inclination angle. The fracture modes of shale at microscopic scale are roughly divided into four categories, similar to I-type fracture (0°), oblique I-type fracture (15°, 45°, 60°, 75°), folded line fracture (30°), and V-type fracture (90°). Natural cracks within the shale have a significant effect on the distribution of stress. Acoustic emission can reflect the stress change and rupture process of shales containing natural cracks with different dip angles at microscopic scale; the presence of natural cracks has a significant effect on AE energy and fractal dimension, the magnitude of AE energy increases with increasing stress level and reaches a maximum at 90°, while the value of fractal dimension is zigzagging up, which is due to the fact that the value of fractal dimension is jointly influenced by the newborn cracks and the native natural cracks.